The influence of career development, organisational culture, and employee engagement on productivity through religiosity as a mediating variable - Anandita, Sevtia; Suhardi, Suhardi; Firdaus, Rahmad (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
Improving work productivity in public service agencies, such as the Population and Civil Registration Office of Bangka Belitung Province, is becoming increasingly crucial in line with the demands for service digitalization and dynamic bureaucratic efficiency. This study aims to analyze the influence of career development, organizational culture, and employee engagement on employee work productivity, with religiosity as a mediating variable. This study uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data were collected through a structured questionnaire distributed to all employees as research respondents. The analysis results show that career development has a positive and significant effect on religiosity and employee work productivity. Conversely, organizational culture and employee engagement do not show a significant effect on either religiosity or work productivity. Other findings reveal that religiosity is able to partially mediate the effect of career development on work productivity, but does not mediate the relationship between other variables. This study confirms that clarity of structured career development and strengthening religious values ??have a strategic role in maintaining stability and improving employee performance in the public service sector.